Extracellular Superoxide Dismutase (EC-SOD) Regulates Gene Methylation and Cardiac Fibrosis During Chronic Hypoxic Stress - Rajgarhia, Ayan; Ayasolla, Kameshwar R.; Zaghloul, Nahla; Lopez Da Re, Jorge M.; Miller, Edmund J.; Ahmed, Mohamed (Frontiers in Cardiovascular Medicine, 2021)
Chronic hypoxic stress induces epigenetic modifications mainly DNA methylation in cardiac fibroblasts, inactivating tumor suppressor genes (RASSF1A) and activating kinases (ERK1/2) leading to fibroblast proliferation and cardiac fibrosis. The Ras/ERK signaling pathway is an intracellular signal transduction critically involved in fibroblast proliferation. RASSF1A functions through its effect on downstream ERK1/2. The antioxidant enzyme, extracellular superoxide dismutase (EC-SOD), decreases oxidative stress from chronic hypoxia, but its effects on these epigenetic changes have not been fully explored. To test our hypothesis, we used an in-vitro model: wild-type C57B6 male mice (WT) and transgenic males with an extra copy of human hEC-SOD (TG). The studied animals were housed in hypoxia (10% O2) for 21 days. The right ventricular tissue was studied for cardiac fibrosis markers using RT-PCR and Western blot analyses. Primary C57BL6 mouse cardiac fibroblast tissue culture was used to study the in-vitro model, the downstream effects of RASSF-1 expression and methylation, and its relation to ERK1/2. Our findings showed a significant increase in cardiac fibrosis markers: Collagen 1, alpha smooth muscle actin (ASMA), and SNAIL, in the WT hypoxic animals as compared to the TG hypoxic group (p < 0.05). The expression of DNA methylation enzymes (DNMT 1&3b) was significantly increased in the WT hypoxic mice as compared to the hypoxic TG mice (p < 0.001). RASSF1A expression was significantly lower and ERK1/2 was significantly higher in hypoxia WT compared to the hypoxic TG group (p < 0.05). Use of SiRNA to block RASSF1A gene expression in murine cardiac fibroblast tissue culture led to increased fibroblast proliferation (p < 0.05). Methylation of the RASSF1A promoter region was significantly reduced in the TG hypoxic group compared to the WT hypoxic group (0.59 vs. 0.75, respectively). Based on our findings, we can speculate that EC-SOD significantly attenuates RASSF1A gene methylation and can alleviate cardiac fibrosis induced by hypoxia.